Design an electronic system use the audio fingerprint to access virtual classroom using Artificial Neural Networks - Hammad, Mahgoub H.; Mohammed, Alsadig; Eldow, Moawia E. (2015 International Conference on Computer, Communications, and Control Technology (I4CT), 2015)
This study aims at designing and developing an electronic system that depends on the Audio Fingerprint to access the learning management system (Blackboard) by students of King Khalid University, as a complement to the current system based on username and password only. [1] The vulnerability of the former used system is represented in the possible accessibility of non authorized peoples to the system who enjoy all available academic services through the utilization of the tests and assignments and participate in the forums and discussions. They deceive the subject teacher. This affects the credibility of the final grades and students' assessment. The system proposed by the researcher works to avoid this gap where it becomes possible to check the students' identity and the authorized users by verifying the Audio Fingerprint through certain words the person utters, using some phrases and replications. The program, then, checks the imprint of the student's voice through an algorithm matching which was designed by the researcher. The results shows that the percentages of matching to the recorded sounds were 94% in ordinary circumstances and 98.5% in an equipped studio. The study recommends the use of the system in all virtual learning centers. In addition, the biometrics can be developed and utilized for academic authentication purposes.